Semantic and Pragmatic Analysis of the Use of Modal Verbs in Literary Discourse: Pouvoir — Meaning and Usage in the Novel Léon l’Africain by Amin Maalouf. - Guerch, Mohammed Rami; Hadjab , Lamia (El Omda in Linguistics and Discourse Analysis, 2023)
The semantic analysis of modal verbs (pouvoir and devoir) demonstrates the polysemy, or “plurivocity,” that characterizes them. These verbs exhibit different meaning effects that can be described, respectively, in logical terms of possibility and necessity. This article aims to explore the modal verb pouvoir on both the syntactic and semantic levels in Amin Maalouf’s novel Léon l’Africain, with the objective of identifying discursive meaning effects as they are considered within their “context.”